Thomas Byström 1772- 1839 - Marvia, Einari (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1983)
Creative music in Finland first had its well-known representatives in the late 1700's but the meager cultural climate led most of them to live in the mother country at that time, Sweden. Thomas Byström received his elementary musical education in Helsinki but was sent as a 13-year-old to Reval for his secondary education, this town also offering considerably better possibilities for studies in music than his home town. Already in 1786 Byström performed as a piano soloist in the first concert held in Helsinki. In the following year he enlisted rather surprisingly in the Royal Artillery and Engineers Academy in St. Petersburg where he graduated as an officer in 1791. Apparently he chose a military career on account of St. Petersburg also offering opportunities for higher musical education. which is also suggested by the fact that when Byström enlisted in the Swedish Army in 1792 he was quickly elected as member of the Royal Academy of Music (1794). As proof of his ability he probably presented a number of ballads, the first being published in 1794-95 in the musical periodical Musikaliskt tidsfördrif. These maiden works were small stanzaic ballads but eventually Byström extended their form, each stanza having its own characteristic. They were usually of a melancholy nature; a frequent theme being childhood memories. Altogether nine ballads by Byström have survived. His gifts as a pianist are apparent in his two most comprehensive piano compositions. Air Russe Variée and Polonoise. Nevertheless, Byström's most important work is three sonatas for piano (harpsichord) with violin accompaniment from 1801. As aide-de-camp to the king, Byström accompanied the expeditions in Pommerania and to the Island of Åland. and also held the post of secretary to the Royal Military Academy from 1806 until his death. In 1813 he was promoted to Lieutenant-colonel but under the new king he fell into disfavour and was reduced to giving piano lessons at the Royal Academy of Music from 1818 to 1833. However, he had the honour of teaching music to the musical Crown-prince Oscar. who reigned as king from 1844 to 1857. In 1827 Byström was allowed to continue his military career as an official at the Military Academy.